2013
DOI: 10.1186/1423-0127-20-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA signatures in mice exposed to lipoteichoic acid

Abstract: BackgroundPreviously, we had identified a specific whole blood–derived microRNAs (miRNAs) signature in mice following in vivo injection of lipopolysaccharide (LPS) originated from Gram-negative bacteria. This study was designed to profile the circulating miRNAs expression in mice exposed to lipoteichoic acid (LTA) which is a major component of the wall of Gram-positive bacteria.ResultsC57BL/6 mice received intraperitoneal injections of 100 μg of LTA originated from Bacillus subtilis, Streptococcus faecalis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In this study, we found that none of the up-regulated miRNAs was expressed in the WBCs. Previously, we had demonstrated a dose- and time-dependent up-regulation of 8 (let-7d, miR-15b, miR-16, miR-25, miR-92a, miR-103, miR-107, and miR-451) and 4 (miR-451, miR-668, miR-1902, and miR-1904) circulating miRNA targets in mice following injection of LPS [11] and LTA [12], respectively. However, in the CLP-based model of sepsis, only miR-16 was up-regulated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we found that none of the up-regulated miRNAs was expressed in the WBCs. Previously, we had demonstrated a dose- and time-dependent up-regulation of 8 (let-7d, miR-15b, miR-16, miR-25, miR-92a, miR-103, miR-107, and miR-451) and 4 (miR-451, miR-668, miR-1902, and miR-1904) circulating miRNA targets in mice following injection of LPS [11] and LTA [12], respectively. However, in the CLP-based model of sepsis, only miR-16 was up-regulated.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, circulating microRNAs (miRNAs) in the serum were found to show specific expression patterns, and these patterns suggested that serum miRNAs contain fingerprints for various diseases; therefore, circulating miRNAs are considered promising markers for the detection of diseases [10][12]. miRNAs are approximately 22-nt-long small regulatory RNA molecules that modulate the activity of specific mRNA targets and play important roles in a wide range of physiologic and pathologic processes [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…DENV infection symptoms are not sufficiently specific to allow clinical differentiation from other acute febrile illnesses, especially in areas where multiple tropical diseases such as malaria, yellow fever, West Nile disease and Saint Louis encephalitis are endemic [6] . There are several dengue vaccine candidates under development, but none is licensed and available [7] . Additionally, there is no specific treatment for dengue, and the most effective protective measures are those that lower the risk of mosquito bites.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, miR-866-5p was increased in human monocyte-derived macrophages in response to several Mycobacterium avium subsp. hominissuis infection [ 23 ], while a significant increase in miR-668 was observed in circulation following lipoteichoic acid injection, a major component of the wall of gram-positive bacteria [ 24 ].…”
Section: Discussionmentioning
confidence: 99%